2003
DOI: 10.1177/0021955x03039003002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Evolution of PIR Foams in the Context of the Phase Out of HCFCs

Abstract: PIR foams are known for their outstanding fire properties and for their good insulation performances. The fire behavior can be attributed to the aromatic structure of the isocyanurate ring and to the nonflammability of the blowing agent that is used nowadays.For environmental reasons, HCFC-141b will have to be phased out as of 01.01.2003 for the production of PIR laminates boards, in Europe and in the United States. This evolution represents a challenge for the producers as they need to find a high performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Since the pentane adds no more than 3–5 wt % to the overall weight and thus barely any fuel or increased EHC, the fire behaviour of a RPUF is determined mainly by the solid polymer and not by the gas phase [8]. Investigations of pentane- and HFC 365mfc-blown foams have revealed that they do not differ fundamentally from CFC-11- or HCFC 141b-blown foams in their fire behaviour [47,48].…”
Section: Resultsmentioning
confidence: 99%
“…Since the pentane adds no more than 3–5 wt % to the overall weight and thus barely any fuel or increased EHC, the fire behaviour of a RPUF is determined mainly by the solid polymer and not by the gas phase [8]. Investigations of pentane- and HFC 365mfc-blown foams have revealed that they do not differ fundamentally from CFC-11- or HCFC 141b-blown foams in their fire behaviour [47,48].…”
Section: Resultsmentioning
confidence: 99%